Adapting the Scale for Spiritual Intelligence to Turkish - Özge Erduran-Tekin; Halil Eksi (Spiritual Psychology and Counseling)
The purpose of this study is to adapt the Scale for Spiritual Intelligence Scale developed by Kumar and Mehta (2011) into Turkish and to examine its reliability and validity. Data have been collected from four different study groups involving a total of 1,098 high school students (440 females and 658 males). In Turkey, the exploratory factor analysis of the Scale for Spiritual Intelligence’s original structure, which consists of six factors, only appears to have occurred in four cases. The goodness-of-fit statistics obtained as a result of the confirmatory factor analysis performed on one sample using this structure are X2 = 335.17, SD = 145 (X2 / SD = 2.33), RMSEA = 0.052, SRMR = 0.049, GFI = 0.93, CFI = 0.90, AGFI = 0.91. Whether or not a statistically significant difference exists in the scores for the lower and upper 27th-percentile groups was examined in order to look at the discriminators of the scale; a statistically significant difference has been detected in favor of the upper segment. As a result of the criterion validity study, a significant positive correlation has been found between the Scale for Spiritual Intelligence and the Meaning in Life Scale (Demirbaş, 2010). According to the obtained linguistic equivalence results, the Turkish form of the scale is seen to be equivalent to the original English form. Cronbach’s alphas of internal consistency and reliability were calculated as .86 and .85 for both samples. Research results reveal the Turkish form of Scale for Spiritual Intelligence to be a valid and reliable instrument that can be used in scientific studies to be carried out in Turkey.